Marketing: The Backbone of Business and Customer Satisfaction - Chand, Bhan Bahadur (KVM Research Journal, 2025)
Marketing plays a pivotal role in the success and sustainability of any business. It serves as the backbone that connects organizations with their target customers, identifies their needs, and delivers value through products and services. Effective marketing strategies not only enhance brand visibility and sales but also significantly influence customer satisfaction, loyalty, and long-term engagement. According to Kotler and Keller (2020), businesses that prioritize marketing initiatives and focus on understanding consumer behavior are better positioned to achieve competitive advantage. This study explores the relationship between marketing practices and customer satisfaction, highlighting the importance of market research, digital marketing, personalized communication, and customer-centric strategies. The findings suggest that businesses integrating comprehensive marketing approaches into their operations experience improved customer satisfaction, stronger brand loyalty, and sustainable growth in today’s competitive marketplace.